Spectral analysis of Urvara–Yalode bright areas on Ceres suggests a new aromatic organic material and Fe-carbonate - S. D’Urzo; A. Raponi; M.C. De Sanctis; B. Ranieri; M. Ciarniello; F.G. Carrozzo; M. Ferrari; E. Ammanito; A. Frigeri; S. De Angelis; M. Formisano (Icarus, 2027)

Making Waves: towards a harmonized approach for monitoring antimicrobial resistance in European surface waters - P. Krzeminski; C.U. Schwermer; M. Anglès d’Auriac; H. Bürgmann; H. Schmitt; J. Vierheilig; M. Gjeitnes; S.J. Moe; X. Bellanger; R. Carapeto García; P. Crespo Iniesta; C. Dagot; et al. (Water Research, 2026)

ISRM Suggested Methods for Triaxial Compression Testing of Shales and Mudstones - R. Ewy; E. Fjær; P. Delage; D. Dewhurst; J. Dudley; A. Ferrari; S. Giger; M. Soldal; J. Stenebråten; B. Crawford; S. Fontoura; L. Grande (Rock Mechanics and Rock Engineering, 2026)

Space-dependent continuous time random walk for soil moisture modeling - M.C. Bovier; S. Fedotov; S. Ferraris; A. Gentile; B. Toaldo (Advances in Water Resources, 2026)

Association of meeting the 24-hour movement guidelines with heart rate variability in adults - Bruna T. C. Saraiva; William R. Tebar; Debora T. Furuta; Stefany C. B. Silva; Ewerton P. Antunes; Guilherme Sousa; Gerson Ferrari; Luiz Carlos M. Vanderlei; Diego Giulliano Destro Christofaro (European Journal of Applied Physiology, 2026)

Scaling what works: a collaborative capacity-building program tailored to optimize resources and scale evidence-based interventions for cancer prevention and control - Mary Wangen; Jingle Xu; Amy Tran; Elizabeth A. Rohan; Prajakta Adsul; Cam Escoffery; Renée M. Ferrari; Nikki Hayes; Cari Herington; Katie Jones; Jaron Hoani King; Julie Kranick; et al. (Cancer Causes & Control, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Tracing arsenic and antimony in mining-impacted environments: New insights from antimony isotopes - Colin Ferrari; Kevin B. White; Carol J. Ptacek; David W. Blowes (Chemical Geology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Measurement of the 244Cm neutron capture cross section at the n_TOF facility at CERN - V. Alcayne; A. Kimura; E. Mendoza; D. Cano-Ott; O. Aberle; F. Álvarez-Velarde; S. Amaducci; J. Andrzejewski; L. Audouin; V. Babiano-Suarez; M. Bacak; M. Barbagallo; et al. (Annals of Nuclear Energy, 2026)

Assessment of wildfire-induced hydrological changes in the south andes mountains of chile - G. Alejandra Stehr; V. Nicole Vyhmeister; C. Efraín Duarte; Francisco Nájera-De Ferrari; Vicente Saenger; Felipe Aburto; Rafael Rubilar; Carolina Merino-Guzmán; B. Francisco Matus (Journal of Hydrology, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Patient preferences and perceived barriers to follow-up care in a pharmacy-based colorectal cancer screening program: a national survey - Jessie Schwartz; Mary Wangen; Olufeyisayo O. Odebunmi; Austin Waters; Renée Ferrari; Macary Marciniak; Alison T. Brenner; Stephanie B. Wheeler; Parth D. Shah (Cancer Causes & Control, 2025)

Analysis of tight junction protein dynamics by immunohistochemistry in porcine intestinal epithelial cells (IPEC-J2) cells exposed to osmotic stress - B. Passeri; P. Borghetti; M. Andrani; M. Di Pentima; A. Luppi; E. De Angelis; V. Cavalli; L. Ferrari; R. Saleri (Journal of Comparative Pathology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Spindle cell rhabdomyosarcoma in a cockatiel (Nymphicus hollandicus) - Tainah P. Dal Pont; Igor R. Santos; Vanessa C. Pereira; Flávia E. Ferrari; Victória R.Q. Schmidt; Marcele B. Bandinelli; Marcelo Meller Alievi; Saulo P. Pavarini (Journal of Comparative Pathology, 2025)

Transcriptional profiling of Fraxinus excelsior leaves during the early infection phase of ash dieback - Renata Callegari Ferrari; Victor Chano; Karuna Shrestha; Tania Dominguez-Flores; Maia Ridley; Barbara Fussi; Hannes Seidel; Oliver Gailing; Katharina B. Budde (Journal of Plant Diseases and Protection, 2025)
Ash dieback (ADB) has been causing the progressive decline of Fraxinus excelsior trees throughout Europe, urging research and forest management to develop strategies to combat ADB. A genetically heritable component in susceptibility to this fungal disease was reported in common gardens. Thus, exploring the molecular basis of ADB susceptibility will further support breeding initiatives in the future. We performed transcriptional profiling of infected and uninfected leaves from two ash genotypes with different susceptibility to Hymenoscyphus fraxineus . Leaf rachises were sampled one week following inoculation. Differential gene expression analysis was performed to compare between treatments in each genotype (individual response) or in genotypes and treatments combined (common response). Due to the heterogeneity in the response, only DEGs were discussed that passed stringent assessment. Our results revealed that UW1, the most susceptible genotype, showed a total of 515 differentially expressed genes (DEGs), some of them possibly suggesting a self-control mechanism, hindering an effective immune response and causing increased susceptibility. On the other hand, FAR3, the least susceptible genotype with 230 DEGs, seemed to induce a contained but more efficient response, hinting toward a salicylic acid-mediated process and activating pathogen-related (like) proteins as thaumatin-like, peroxidases, and chitinases. In the common response, 512 DEGs were modulated and transcripts from the phenylpropanoid pathway were commonly altered in both genotypes. Altogether, this work comprised an initial transcriptional exploration including two selected genotypes with distinct susceptibility to ADB, however, the heterogenous response indicated the need to further improve the experimental inoculation approach. Exploring gene expression patterns in ADB susceptibility holds promise to reveal early response mechanisms, and new markers related to susceptibility, as well as to contribute to developing strategies that may help contain ADB.

Stochastic model for subsurface water flow in Swiss catchments - M.C. Bovier; S. Fedotov; S. Ferraris; A. Gentile; B. Toaldo (Advances in Water Resources, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

LGBTQ+ cancer: priority or lip service? A qualitative content analysis of LGBTQ+ considerations in U.S. state, jurisdiction, and tribal comprehensive cancer control plans - Austin R. Waters; Madeline H. Bono; Mayuko Ito Fukunaga; Manal Masud; Megan A. Mullins; Ryan Suk; Meghan C. O’Leary; Swann A. Adams; Renée M. Ferrari; Mary Wangen; Olufeyisayo O. Odebunmi; Sarah H. Nash; et al. (Cancer Causes & Control, 2024)

Evolution of water content and suction of Opalinus Clay from recovery at the drilling site to handling in the laboratory - Angelica Tuttolomondo; Alessio Ferrari; Silvio B. Giger; Lyesse Laloui (International Journal of Rock Mechanics and Mining Sciences, 2024)

Combination of pH-shifting, ultrasound, and heat treatments to enhance solubility and emulsifying stability of rice protein isolate - Daniela E. Igartúa; M. Celeste Dichano; Sofia B. Ferrari; Gonzalo G. Palazolo; Dario M. Cabezas (Food Chemistry, 2024)

Patient preferences for the design of a pharmacy-based colorectal cancer screening program - Alison T. Brenner; Austin R. Waters; Mary Wangen; Catherine Rohweder; Olufeyisayo Odebunmi; Macary Weck Marciniak; Renée M. Ferrari; Stephanie B. Wheeler; Parth D. Shah (Cancer Causes & Control, 2023)
Purpose To assess preferences for design of a pharmacy-based colorectal cancer (CRC) screening program (PharmFIT™) among screening-eligible adults in the United States (US) and explore the impact of rurality on pharmacy use patterns (e.g., pharmacy type, prescription pick-up preference, service quality rating). Methods We conducted a national online survey of non-institutionalized US adults through panels managed by Qualtrics, a survey research company. A total of 1,045 adults (response rate 62%) completed the survey between March and April 2021. Sampling quotas matched respondents to the 2010 US Census and oversampled rural residents. We assessed pharmacy use patterns by rurality and design preferences for learning about PharmFIT™; receiving a FIT kit from a pharmacy; and completing and returning the FIT kit. Results Pharmacy use patterns varied, with some notable differences across rurality. Rural respondents used local, independently owned pharmacies more than non-rural respondents (20.4%, 6.3%, p < 0.001) and rated pharmacy service quality higher than non-rural respondents. Non-rural respondents preferred digital communication to learn about PharmFIT™ (36% vs 47%; p < 0.001) as well as digital FIT counseling (41% vs 49%; p = 0.02) more frequently than rural participants. Preferences for receiving and returning FITs were associated with pharmacy use patterns: respondents who pick up prescriptions in-person preferred to get their FIT (OR 7.7; 5.3–11.2) and return it in-person at the pharmacy (OR 1.7; 1.1–2.4). Conclusion Pharmacies are highly accessible and could be useful for expanding access to CRC screening services. Local context and pharmacy use patterns should be considered in the design and implementation of PharmFIT™.

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Non-toxic acid-free glyoxal fixative for veterinary histopathology, immunohistochemistry and molecular analysis - V. Zappulli; F. Torrigiani; P. Detillo; S. Iussich; M. Rondena; C. Gola; L. MInoli; E. Morello; E.I. Ferraris; A. Rigillo; B. Bussolati (Journal of Comparative Pathology, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

TimeFISH : Long‐term assessment of reef fish assemblages in a transition zone in the Southwestern Atlantic - Juan P. Quimbayo; Lucas T. Nunes; Fernanda C. Silva; Antônio B. Anderson; Diego R. Barneche; Angela M. Canterle; Isadora Cord; Andrea Dalben; Débora S. Ferrari; Luisa Fontoura; Thiago M. J. Fiuza; Ana M. R. Liedke; et al. (Ecology, 2023)
The TimeFISH database provides the first public time‐series dataset on reef fish assemblages in the southwestern Atlantic (SWA), comprising 15 years of data (2007–2022) based on standardized Underwater Visual Censuses (UVCs). The rocky reefs covered by our dataset are influenced by pronounced seasonal cycles of ocean temperatures with warm tropical waters from the Brazil Current in the summer (~27°C) and colder waters from the La Plata River Plume discharge and upwelling from the South Atlantic Central Water in the winter (~18°C). These oceanographic conditions characterize this area as the southernmost tropical–subtropical climatic transition zone in the Atlantic Ocean. As a result, reef fish assemblages are comprised of both tropical and subtropical species. All records included in TimeFISH were collected using UVCs, a nondestructive method that allows the estimation of fish species richness, abundance, and body size distributions. UVCs were performed through 40 m 2 belt transects by scuba diving in nine locations along the southern Brazilian coast (25–29°S). Four of these locations lie within the boundaries of the no‐entry Arvoredo Marine Biological Reserve, where fishing and recreational activities are forbidden, and the remaining locations are unprotected from these activities. During each belt transect, a diver swam at a constant depth above and parallel to the reef, identifying fish species, counting the number of individuals, and estimating the total body length (Lt in cm) of all detected individuals. All fish individuals in the water column (up to 2 m above the substratum) and at the bottom were targeted. In total, 202,965 individuals belonging to 163 reef fish species and 53 families were recorded across 1857 UVCs. All survey campaigns were funded by either public or mixed capital (private–public) sources, including seven grants from the Brazilian federal and Santa Catarina state governments. Part of the data has already been used in multiple MS.c. and Ph.D. theses and scientific articles. TimeFISH represents an important contribution for future studies aiming to examine temporal and spatial variations of reef fish assemblages in transition zones. No copyright restrictions apply to the use of this data set, other than citing this publication.

Long-term use of pharmacological treatment in Alzheimer’s disease: a retrospective cohort study in real-world clinical practice - G Lombardi; N Lombardi; A Bettiol; G Crescioli; C Ferrari; G Lucidi; C Polito; V Berti; V Bessi; S Bagnoli; B Nacmias; A Vannacci; et al. (European Journal of Clinical Pharmacology, 2022)

Extinct groundwater discharge locality in the Eldorado Valley; eastern Mojave Desert, Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Paul McBurnett; David Ferrari; Giavanna M. Fernandez; Juan Garcia-Hernandez; Bailey D. Kesl; Flavio W. Rodriguez; Sean G. Torres (Journal of Sedimentary Environments, 2022)

Digital biomarkers and sex impacts in Alzheimer’s disease management — potential utility for innovative 3P medicine approach - Robbert L. Harms; Alberto Ferrari; Irene B. Meier; Julie Martinkova; Enrico Santus; Nicola Marino; Davide Cirillo; Simona Mellino; Silvina Catuara Solarz; Ioannis Tarnanas; Cassandra Szoeke; Jakub Hort; et al. (EPMA Journal, 2022)
Digital biomarkers are defined as objective, quantifiable physiological and behavioral data that are collected and measured by means of digital devices. Their use has revolutionized clinical research by enabling high-frequency, longitudinal, and sensitive measurements. In the field of neurodegenerative diseases, an example of a digital biomarker-based technology is instrumental activities of daily living (iADL) digital medical application, a predictive biomarker of conversion from mild cognitive impairment (MCI) due to Alzheimer’s disease (AD) to dementia due to AD in individuals aged 55 + . Digital biomarkers show promise to transform clinical practice. Nevertheless, their use may be affected by variables such as demographics, genetics, and phenotype. Among these factors, sex is particularly important in Alzheimer’s, where men and women present with different symptoms and progression patterns that impact diagnosis. In this study, we explore sex differences in Altoida’s digital medical application in a sample of 568 subjects consisting of a clinical dataset (MCI and dementia due to AD) and a healthy population. We found that a biological sex-classifier, built on digital biomarker features captured using Altoida’s application, achieved a 75% ROC-AUC (receiver operating characteristic — area under curve) performance in predicting biological sex in healthy individuals, indicating significant differences in neurocognitive performance signatures between males and females. The performance dropped when we applied this classifier to more advanced stages on the AD continuum, including MCI and dementia, suggesting that sex differences might be disease-stage dependent. Our results indicate that neurocognitive performance signatures built on data from digital biomarker features are different between men and women. These results stress the need to integrate traditional approaches to dementia research with digital biomarker technologies and personalized medicine perspectives to achieve more precise predictive diagnostics, targeted prevention, and customized treatment of cognitive decline.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Stereotactic radiation therapy in oligometastatic colorectal cancer: outcome of 102 patients and 150 lesions - V. Dell’Acqua; A. Surgo; F. Kraja; J. Kobiela; Maria Alessia Zerella; P. Spychalski; S. Gandini; C. M. Francia; D. Ciardo; C. Fodor; A. M. Ferrari; G. Piperno; et al. (Clinical & Experimental Metastasis, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

A combined stochastic analysis of mean daily temperature and diurnal temperature range - B. Sirangelo; T. Caloiero; R. Coscarelli; E. Ferrari (Theoretical and Applied Climatology, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Marine infrastructure supports abundant, diverse fish assemblages at the expense of beta diversity - A. G. Porter; R. L. Ferrari; B. P. Kelaher; S. D. A. Smith; R. A. Coleman; M. Byrne; W. Figueira (Marine Biology, 2018)

Diversity in a pea (Pisum sativum) world collection for key agronomic traits in a rain-fed environment of Southern Europe - P. Annicchiarico; M. Romani; G. Cabassi; B. Ferrari (Euphytica, 2017)

Temporal Analysis of Rainfall Categories in Southern Italy (Calabria Region) - T. Caloiero; R. Coscarelli; E. Ferrari; B. Sirangelo (Environmental Processes, 2017)

A stochastic model for the analysis of maximum daily temperature - B. Sirangelo; T. Caloiero; R. Coscarelli; E. Ferrari (Theoretical and Applied Climatology, 2017)

Trend analysis of monthly mean values and extreme indices of daily temperature in a region of southern Italy - T. Caloiero; R. Coscarelli; E. Ferrari; B. Sirangelo (International Journal of Climatology, 2017)
The analyses of temperature extremes can be very useful because they are highly representative of the climatic tendency of an area. In this study, 19 temperature series registered in southern Italy have been analysed for detecting trends through the Mann–Kendall non‐parametric test. The tendencies have been detected since 1951 for the maximum and minimum monthly temperatures and for several indices of daily extremes. As a result, the minimum and maximum monthly temperatures mainly denote a positive trend for spring and summer months and a marked negative one in September. Moreover, the trend analysis on the extreme temperature indices shows opposite behaviours: a clear positive tendency in the frequency and intensity of the highest values and some negative trends for the lowest ones.

Probucol attenuates overt pain-like behavior and carrageenan-induced inflammatory hyperalgesia and leukocyte recruitment by inhibiting NF-кB activation and cytokine production without antioxidant effects - Amanda Z. Zucoloto; Marília F. Manchope; Larrisa Staurengo-Ferrari; José C. Alves-Filho; Thiago M. Cunha; Maísa M. Antunes; Gustavo B. Menezes; Fernando Q. Cunha; Rubia Casagrande; Waldiceu A. Verri (Inflammation Research, 2017)

Stochastic analysis of long dry spells in Calabria (Southern Italy) - B. Sirangelo; T. Caloiero; R. Coscarelli; E. Ferrari (Theoretical and Applied Climatology, 2017)

Cystic fibrosis in Afro-Brazilians: XK haplotypes analysis supports the European origin of p.F508del mutation - D. A. S. de Souza; F. R. Faucz; R. B. de Alexandre; M. A. Santana; E. L. S. de Souza; F. J. C. Reis; L. Pereira-Ferrari; V. S. Sotomaior; L. Culpi; J. A. Phillips; S. Raskin (Genetica, 2017)

Comparison of abdominal adiposity and overall obesity in relation to risk of small intestinal cancer in a European Prospective Cohort - Yunxia Lu; Amanda J. Cross; Neil Murphy; Heinz Freisling; Ruth C. Travis; Pietro Ferrari; Verena A. Katzke; Rudolf Kaaks; Åsa Olsson; Ingegerd Johansson; Frida Renström; Salvatore Panico; et al. (Cancer Causes & Control, 2016)

Quantifying the response of structural complexity and community composition to environmental change in marine communities - Renata Ferrari; Mitch Bryson; Tom Bridge; Julie Hustache; Stefan B. Williams; Maria Byrne; Will Figueira (Global Change Biology, 2016)
Habitat structural complexity is a key factor shaping marine communities. However, accurate methods for quantifying structural complexity underwater are currently lacking. Loss of structural complexity is linked to ecosystem declines in biodiversity and resilience. We developed new methods using underwater stereo‐imagery spanning 4 years (2010–2013) to reconstruct 3D models of coral reef areas and quantified both structural complexity at two spatial resolutions (2.5 and 25 cm) and benthic community composition to characterize changes after an unprecedented thermal anomaly on the west coast of Australia in 2011. Structural complexity increased at both resolutions in quadrats (4 m 2 ) that bleached, but not those that did not bleach. Changes in complexity were driven by species‐specific responses to warming, highlighting the importance of identifying small‐scale dynamics to disentangle ecological responses to disturbance. We demonstrate an effective, repeatable method for quantifying the relationship among community composition, structural complexity and ocean warming, improving predictions of the response of marine ecosystems to environmental change.

A stochastic model for the analysis of the temporal change of dry spells - B. Sirangelo; T. Caloiero; R. Coscarelli; E. Ferrari (Stochastic Environmental Research and Risk Assessment, 2015)

Analysis of the spatial correlation structure exhibited by daily rainfall in Southern Italy - B. Sirangelo; E. Ferrari (Theoretical and Applied Climatology, 2014)

Investigating the feasibility of using DNA from sloughed skin for individual identification and kinship analysis in humpback whales ( Megaptera novaeangliae ) - S. P. Pierszalowski; M. Ferrari; D. Glockner‐Ferrari; S. Mizroch; P. J. Clapham; B. R. Dickerson (Marine Mammal Science, 2013)

Assessing and promoting old-growthness of forest stands: Lessons from research in Italy - A. Barbati; R. Salvati; B. Ferrari; D. Di Santo; A. Quatrini; L. Portoghesi; D. Travaglini; F. Iovino; S. Nocentini (Plant Biosystems, 2012)

Connectivity of Caribbean coral populations: complementary insights from empirical and modelled gene flow - NICOLA L. FOSTER; CLAIRE B. PARIS; JOHNATHAN T. KOOL; ILIANA B. BAUMS; JAMIE R. STEVENS; JUAN A. SANCHEZ; CAROLINA BASTIDAS; CLAUDIA AGUDELO; PHILLIPPE BUSH; OWEN DAY; RENATA FERRARI; PATRICIA GONZALEZ; et al. (Molecular Ecology, 2012)
Understanding patterns of connectivity among populations of marine organisms is essential for the development of realistic, spatially explicit models of population dynamics. Two approaches, empirical genetic patterns and oceanographic dispersal modelling, have been used to estimate levels of evolutionary connectivity among marine populations but rarely have their potentially complementary insights been combined. Here, a spatially realistic Lagrangian model of larval dispersal and a theoretical genetic model are integrated with the most extensive study of gene flow in a Caribbean marine organism. The 871 genets collected from 26 sites spread over the wider Caribbean subsampled 45.8% of the 1900 potential unique genets in the model. At a coarse scale, significant consensus between modelled estimates of genetic structure and empirical genetic data for populations of the reef‐building coral Montastraea annularis is observed. However, modelled and empirical data differ in their estimates of connectivity among northern Mesoamerican reefs indicating that processes other than dispersal may dominate here. Further, the geographic location and porosity of the previously described east–west barrier to gene flow in the Caribbean is refined. A multi‐prong approach, integrating genetic data and spatially realistic models of larval dispersal and genetic projection, provides complementary insights into the processes underpinning population connectivity in marine invertebrates on evolutionary timescales.

A molecular analysis of the evolutionary relationships in the Callitrichinae, with emphasis on the position of the dwarf marmoset - Horacio Schneider; Jose Antonio R. Bernardi; Divino B. Da Cunha; Claudia H. Tagliaro; Marcelo Vallinoto; Steve F. Ferrari; Iracilda Sampaio (Zoologica Scripta, 2012)
Schneider, H., Bernardi, J. A. R., da Cunha, D. B., Tagliaro, C. H., Vallinoto, M., Ferrari, S. F. & Sampaio, I. (2011). A molecular analysis of the evolutionary relationships in the Callitrichinae, with emphasis on the position of the dwarf marmoset. — Zoologica Scripta , 41 , 1–10. The phylogenetic relationships among the Neotropical primates of the subfamily Callitrichinae (marmosets and tamarins) are controversial, especially with regard to the proposal of a new marmoset genus, Callibella , based on the analysis of sequences of a single mitochondrial gene. In this study, we combine the fast‐evolving mitochondrial Control Region with four nuclear regions containing Alu elements in an attempt to provide a more conclusive assessment of the phylogenetic relationships among the marmosets ( Callithrix , Cebuella and Mico ), with special attention to the validity of Callibella . A large, representative sample of specimens was obtained, which include all the recognized genera and principal morphological and geographic groupings. The results of the analysis indicate unequivocally the existence of three independent lineages, corresponding to the Atlantic Forest ( Callithrix ), Amazonian ( Mico ) and pygmy marmoset ( Cebuella ) groups. The evidence also confirms the monophyletic relationship of the dwarf marmoset ( Callibella ) with the Amazonian marmosets ( Mico ), which indicates conclusively that this taxon is a member of the genus Mico , upholding the original description of the species as Mico humilis .

Energy balance of juvenile Cyprinus carpio after a short-term exposure to sublethal water-borne cadmium - L. Ferrari; B. L. Eissa; A. Salibián (Fish Physiology and Biochemistry, 2011)

Use of a comprehensive numerical model to improve biventricular pacemaker temporization in patients affected by heart failure undergoing to CRT-D therapy - A. Di Molfetta; L. Santini; G. B. Forleo; M. Cesario; C. Tota; M. Sgueglia; D. Sergi; G. Ferrari; F. Romeo (Medical & Biological Engineering & Computing, 2010)

Anti N1 Cross-Protecting Antibodies Against H5N1 Detected in H1N1 Infected People - E. Frobert; M. Bouscambert-Duchamp; V. Escuret; S. Mundweiler; M. Barthélémy; F. Morfin; M. Valette; C. Gerdil; B. Lina; O. Ferraris (Current Microbiology, 2010)

Comparative Genetic Diversity of Wild and Captive Populations of the Bare-Faced Curassow (Crax fasciolata) Based on Cross-Species Microsatellite Markers: Implications for Conservation and Management - Evonnildo C. Gonçalves; Stephen F. Ferrari; Heitor B. Bastos; Anita Wajntal; Alexandre Aleixo; Maria Paula C. Schneider (Biochemical Genetics, 2010)

Quantitative Behavioral Parameters as Toxicity Biomarkers: Fish Responses to Waterborne Cadmium - B. L. Eissa; N. A. Ossana; L. Ferrari; A. Salibián (Archives of Environmental Contamination and Toxicology, 2010)

Records of large earthquakes in lake sediments along the North Anatolian Fault, Turkey - X. Boës; S. B. Moran; J. King; M. N. Cağatay; A. Hubert-Ferrari (Journal of Paleolimnology, 2010)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Monitoring and assessing old‐growth forest stands by plot sampling - P. Corona; C. Blasi; G. Chirici; L. Facioni; L. Fattorini; B. Ferrari (Plant Biosystems, 2010)

Dexmedetomidine chemical restraint of two raptor species undergoing inhalation anaesthesia - B. Santangelo; D. Ferrari; I. Di Martino; A. Belli; C. Cordella; A. Ricco; S. Troisi; G. Vesce (Veterinary Research Communications, 2009)

Abnormal meiosis in tetraploid genotypes ofBrachiaria brizantha (Poaceae) induced by colchicine: its implications for breeding - A. B. Mendes-Bonato; M. Ferrari Felismino; A. M. Souza Kaneshima; C. Pessim; V. Calisto; M. Suely Pagliarini; C. Borges do Valle (Journal of Applied Genetics, 2009)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Closed-tube DNA extraction using a thermostable proteinase is highly sensitive, capable of single parasite detection - B. C. Ferrari; M. L. Power; P. L. Bergquist (Biotechnology Letters, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Behavioral Alterations in Juvenile Cyprinus carpio (Linnaeus, 1758) Exposed to Sublethal Waterborne Cadmium - B. L. Eissa; A. Salibián; L. Ferrari (Bulletin of Environmental Contamination and Toxicology, 2006)

Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: the European Prospective Investigation into Cancer and Nutrition - S. Rinaldi; P. H. M. Peeters; I. D. Bezemer; L. Dossus; C. Biessy; C. Sacerdote; F. Berrino; S. Panico; D. Palli; R. Tumino; K. T. Khaw; S. Bingham; et al. (Cancer Causes & Control, 2006)

Recognition and signalling in the cell wall: The case of endopolygalacturonase, PGIP and oligogalacturonides - B Mattei; R Galletti; C Manfredini; D Pontiggia; G Salvi; S Spadoni; C Caprari; S Ferrari; D Bellincampi; F Cervone; G De Lorenzo (Plant Biosystems, 2005)

A Theoretical Model for the Margination of Particles within Blood Vessels - P. Decuzzi; S. Lee; B. Bhushan; M. Ferrari (Annals of Biomedical Engineering, 2005)

Functional foods, herbs and nutraceuticals: towards biochemical mechanisms of healthy aging - Carlos K. B. Ferrari (Biogerontology, 2004)

Diet of a muriqui group (Brachyteles arachnoides) in continuous primary forest - Oswaldo de Carvalho Jr; Stephen F. Ferrari; Karen B. Strier (Primates, 2004)

Acetylcholinesterase assay may predict cognitive response of Alzheimer patients to eptastigmine treatment - B. P. Imbimbo; M. Nicoli; C. Martini; G. P. Tomelleri; P. Martelli; G. P. Ferrari; G. Gambina (European Journal of Clinical Pharmacology, 1998)

Reactivation in calves ofBovid herpesvirus 2 latent infection - G. Castrucci; M. Ferrari; F. Frigeri; S. Ranucci; V. Cilli; B. Tesei; L. Rampichini (Archives of Virology, 1982)